How can health systems sustain lessons drawn from emergency contexts? Evidence from Colombia - Simon Turner; Mary Ruth Guevara Maldonado (PLoS ONE, 2025)
The Covid-19 pandemic demanded rapid adaptation to health systems internationally, but little is known about the sustained value of the approaches to learning adopted. How does ongoing environmental turbulence influence the lessons drawn from health system responses to pandemics? To address this question, we engage with, and further develop, Levitt and March’s highly cited perspective on experiential learning by analyzing Colombian healthcare professionals’ experiences gathered during semi-structured interviews. Interviews included representatives of national government, service providers, administrative staff, clinicians, including physicians and nurses, professional associations, and academics. Aspects from the macro, meso, and micro contexts associated with the sustainability of organizational learning were identified. At the macro level, reform efforts seem to overlook lessons learned from the pandemic and divert the attention of key actors. At the meso level, leadership uses success stories to motivate teams, but financial challenges and absence of formal evaluations hinder the sustainability of innovations. At the micro level, there is a diminished workforce capacity, some concerns about virtual professional training and difficulties to address mental health issues is difficult due to stoic professional identities, unrelenting tempo of medical work, and institutional encouragement. This study extends Levitt and March’s organizational learning framework to include environmental turbulence as a factor influencing learning. It highlights that a turbulent context simultaneously triggers learning processes while being a precursor to the interpretation of experiences. The research concludes there are additional moderating variables for organizational learning like human resource capacities, political cycles, and infrastructure continuity, which relate to professional pressures to “turn the page” on the pandemic, the patchy resourcing of new initiatives at the organizational level, and the distraction of health reform.